Behavioral Pattern and Communication Style Changes: The Impact of Free Fire Online Game on Children Aged 10-12 Years in Damarwulan Village - Zudistira, Sela; Purnomo, Danang Try; Setyoko, Rahmad (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The Impact of the Free Fire Online Game on Behavior Patterns and speech Styles in Children Aged 10 to 12 Years in Damarwulan Village. Thesis. Buddhist Communication Study Progam, Raden wijaya Wonogiri State College of Buddhism, Central Java. Online games are not only interesting but also make children addicted to playing so they forget about their obligations such as studying, worshiping and eating. The research aims to analyze behavioral patterns, speaking styles and the impact of playing free fire inline games on behavioral patterns and speaking styles in children aged 10 to 12 years in Damarwulan Village. The research uses qualitative methods with a naturalistic approach. The research was carried out in Damarwulan Village, Jepara, Central Java. The research location was chosen because it has potential related to the research title, where elementary school children in Damarwulan Village tend to play mostly online games which couse various kinds of impacts, both positive and negative. Data collection tools in research are observation, interviews, and documentation. Research data analysis techiques use analysis. The results of the study revealed that there were changes in the behavior patterns of the children in Damarwulan Village as a result of playing online games, namely children became lazy, liked to talk to their parents, were undisciplined, and did not care about their surroundings. Changes also occur in children’s speaking styles, which tend to be rude and disrespectful to older people. More than that, online games have more negative impacts than positive impacts for Damarwulan Village children aged 10 to 12 years. Keywords: Free Fire Online Game, Behavior Patterns, Speaking Style